2014
DOI: 10.7763/ijiet.2014.v4.374
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Technology-Enhanced Learning for Computer Programming Courses

Abstract: Abstract-Teaching computing courses is a major challenge for the majority of lecturers in Libyan higher learning institutions. These courses contain numerous abstract concepts that cannot be easily explained using traditional educational methods. This paper describes the rationale, design, development and implementation stages of an e-learning package (including multimedia resources such as simulations, animations, and videos) using the ASSURE model. This training package can be used by students before they at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Mulwa and Kyalo (2013) [33] assert that the attitude of the implements has a significant role in how well ICT is implemented in administration, teaching, and learning. The main barrier to the effective execution of an e-learning project was therefore determined to be a negative attitude against the use of ICT (Othman, Pislaru, Kenan & Impes, 2013) [45] . Additionally, it's important to research and determine how much user attitudes affect how ICT is used in administration, education, and learning.…”
Section: Attitudementioning
confidence: 99%
“…Mulwa and Kyalo (2013) [33] assert that the attitude of the implements has a significant role in how well ICT is implemented in administration, teaching, and learning. The main barrier to the effective execution of an e-learning project was therefore determined to be a negative attitude against the use of ICT (Othman, Pislaru, Kenan & Impes, 2013) [45] . Additionally, it's important to research and determine how much user attitudes affect how ICT is used in administration, education, and learning.…”
Section: Attitudementioning
confidence: 99%
“…According to Drigas and Charami (2014), teaching itself is an art, which is constantly changing depending on the era we live and teach in. However, the improvement of technology for teaching and learning has been found that using technology can benefit to enhance teaching by transforming the process of delivering lecture to the student through the use of technology (Othman, Pislaru & Impes 2014). Another study highlighted that implementation of ICT in the lecture room will change the attitude of the lecturer, which the changes can play important role in integration of ICT will bring a positive influence to the lecturer (Abukhattala, 2016;Alsulami, 2016).…”
Section: Use Of Ictmentioning
confidence: 99%
“…unluckily, old methods of teaching English to EFL students are still in use in the Libyan educational system, and many Libyan teachers are ignorant of this relatively recent trend in language teaching (Belazi & Ganapathy, 2021). Despite the wealth of research on the subject, there have been few studies on the use of blended learning with Libyan EFL students (Othman et al, 2013). Blended learning is thought to help both EFL teachers and learners improve their overall EFL competency by boosting learning practises and harnessing technology to create new learning experiences (Al Bataineh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%